STIMULASI DINI PADA POLA ASUH BERDAMPAK POSITIF TERHADAP PERKEMBANGAN ANAK BAWAH DUA TAHUN - Sri Sukamti Sukamti; Aticeh Aticeh Aticeh; Fauziah Fauziah Fauziah (Jurnal Ilmu dan Teknologi Kesehatan, 2014)
Children are the future generation that needs attention. Parents are responsible to achieve future growth and optimal development. Parenting parents determine the rate of growth and development of children. As the next generation, a child needs to be prepared early. The data showed that only 44.6 percent growth monitoring 4 times or more in the last 6 months. There are still 34.3 percent of children who never weighed in a period of 6 months and there has been no report on the monitoring of the development of children under five. The observations in the village are toddlers who have abnormal head circumference and there are babies and delayed development. This study determine how aspects of stimulation on parenting on child growth "baduta". The study used cross-sectional design, the study sample baduta and parents as much as 120. The result found an appropriate level of growth of 40.8%, 31.7% stimulation needs, needsaffection 52.5% and 6.7% needs a foster. There is a significant relationship fulfillment stimulation (teaser) with child development baduta p = 0.016. Needs sharpening form of stimulation for the development of children from an early age is very important given by a parent or guardian in accordance with the age of the child which includes four aspects of development to produce quality child. For health workers should provide health education to parents how to perform age-appropriate stimulation child development so that parents or caregivers can provide stimulation to the child.